Geographic Information Systems and Applications in Coastal Studies - Zhang, Yuanzhi; Cheng, Qiuming (IntechOpen, 2022)
In recent years, geographic information systems (GIS) and their coastal applications have drawn increasing awareness globally, regionally, and locally. These systems are used to monitor, model, and predict coastal zone issues. New technologies, including advances in GIS platforms and techniques, are being adopted and innovatively applied to coastal environments and disasters, coastal resources, coastal social systems, and coastal urban environments using new algorithms, big data processing, and deep learning approaches. This book examines a variety of GIS applications, providing a comprehensive overview of techniques, approaches, and experiences in GIS for coastal zones.